Between Art and Genre: New Nordic Horror Cinema - Iversen, G. (Gunnar) (2016)
This chapter discusses some of the key films within the new Nordic horror cinema. It examines films from all Nordic countries. Until the horror boom started in 2003, since the origins of Norwegian cinema in the late nineteenth century, only two films had been made that could be considered horrors. In Iceland, no horror movies had been made until 2009, when Julius Kemp directed and co-produced Harpoon: Reykjavik Whale Watching Massacre. 1994 was an important year for Danish horror. Not only did Nightwatch hit the silver screens, but the same year Danish filmmaker Lars von Trier made the first part of his critically acclaimed television series The Kingdom. Few horror films have been made in Finland. Even though a number of different horror films have been made in Sweden, and several since 2000, none has made a bigger impact than Let the Right One In.